PENGARUH MODEL PEMBELAJARAN MEAN END ANALYSIS (MEA) TERHADAP HASIL BELAJAR PPKn SISWA KELAS X SMA 3 RAMBAH HILIR - Darmayanti, Suci; Erlinda, Sri; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was motivated by the low learning outcomes of class X students at SMA 3 Rambah Hilir. The formulation of the problem in this study is whether there is an effect of the use of the Means Ends Analysis (MEA) learning model on the learning outcomes of PPKn class X SMA 3 Rambah Hilir students. This study aims to determine the effect of using the Mean End Analysis (MEA) learning model on the learning outcomes of class X PPKn in SMA 3 Rambah Hilir. This research method is descriptive quantitative. The population of this study were students of class X SMA 3 Rambah Hilir. The sampling technique used in this research was random sampling, where the classes taken in the study were X IPS 1 as the experimental class and X IPS 2 as the control class. Based on the results of the study, it was found that there was an effect of learning outcomes between students using the Mean End Analysis (MEA) model and conventional methods at SMA 3 Rambah Hilir. This can be seen from the results showing t count> t table or <t table (4.12> 2 , 01290) thus there is an effect of the Mean End Analysis (MEA) learning model on the learning outcomes of class X PPKn in SMA 3 Rambah Hilir. The amount of influence after being calculated by the gain test shows that the Mean End Analysis (MEA) learning model has an effect on learning outcomes of 0.16 which means it is in the